Integrated 1H NMR fingerprint with NIR spectroscopy, sensory properties, and quality parameters in a multi-block data analysis using ComDim to evaluate coffee blends. (1st September 2021) - Rocha Baqueta, Michel; Coqueiro, Aline; Henrique Março, Paulo; Mandrone, Manuela; Poli, Ferruccio; Valderrama, Patrícia
Graphical abstract: Highlights: Multi-block data analysis was applied for quality control in the coffee industry. Common Dimensions showed clusters, importance of blocks and their relationships. Metabolites related to cup and roasting profiles of coffee blends were identified. Multi-block data analysis was more valuable than a principal component analysis. Relationships between sensory characteristics and metabolites were established. Abstract: Coffee quality is determined by several factors and, in the chemometric domain, the multi-block data analysis methods are valuable to study multiple information describing the same samples. In this industrial study, the Common Dimension (ComDim) multi-block method was applied to evaluate metabolite fingerprints, near-infrared spectra, sensory properties, and quality parameters of coffee blends of different cup and roasting profiles and to search relationships between these multiple data blocks. Data fusion-based Principal Component Analysis was not effective in exploiting multiple data blocks like ComDim. However, when a multi-block was applied to explore the data sets, it was possible to demonstrate relationships between the methods and techniques investigated and the importance of each block or criterion involved in the industrial quality control of coffee. Coffee blends were distinguished based on their qualities and metabolite composition. Blends with high cup quality and lower roasting degrees were generally differentiated from those with opposite characteristics.